2017
DOI: 10.5812/ijcm.8094
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of Emodin on Growth of SKBR3 Breast Cancer Cells

Abstract: Background: The poor prognosis of breast cancer is due to its resistance to the conventional treatments. Therefore, researchers are studying about herbs which have anticancer effects. Emodin is a hydroxy-anthraquinone that is found in many medicinal plants and has biological and anticancer effects. According to previous studies, it inhibited the growth of cancer cells by apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In another study, it was found that emodin also caused apoptosis in SKBR3 cells via caspases. Caspase -3, -8, and -9 mRNA levels increased in SKBR3 cells after administration of emodin at 25 and 50 µM concentration for 48 h. A significant increase in Bax and reduction in Bcl 2 were also observed [89].…”
Section: Breast Cancermentioning
confidence: 84%
“…In another study, it was found that emodin also caused apoptosis in SKBR3 cells via caspases. Caspase -3, -8, and -9 mRNA levels increased in SKBR3 cells after administration of emodin at 25 and 50 µM concentration for 48 h. A significant increase in Bax and reduction in Bcl 2 were also observed [89].…”
Section: Breast Cancermentioning
confidence: 84%
“…Using MCF-7 and MDA-MB-453 (human cells), Huang et al [40] test the anticancer impact of emodin to decreased endoplasmic reticulum (ER) protein levels and suppressed ER transcriptional activation, which in turn restricted cell growth 20 µmol/L IC 50 for toxicity against MCF-7 cells [40]. The proliferation of SKBR3 (human cells) was checked by Kalkhoran et al [41] and work with an IC 50 value of 25 µmol/L raised the expression of the mRNAs for caspase-3, caspase-8, caspase-9, and Bax, decreased the expression of Bcl-2, and induced apoptosis [41].…”
Section: Anticancer Activity Of Emodin For the Management Of Various ...mentioning
confidence: 99%
“…Scientific studies have also discovered lots of beneficial properties of R. palmatum . As reported, R. palmatum contains a variety of bioactive components such as aloe emodin, chrysophanol, rhein, emodin, and physcion [5] , which have been shown to exhibit significant anti-inflammatory [6–8] , anti-viral [5,9] and anti-tumor activities [10–12] .…”
Section: Introductionmentioning
confidence: 99%